RISING A STAR WITH JAIPONG DANCE IN CEREBRAL PALSY: A CASE REPORT (Proceedings of the World Disability & Rehabilitation Conference, 2025)
Cerebral palsy is a disorder that results in abnormal posture and movement, caused by non-progressive damage to the developing brain. Movement disorders that can be seen include spasticity, flaccidity, impaired coordination and balance. Permanent abnormalities in cerebral palsy are not progressive, but can undergo changes with age and the growth process. Therefore, the role of a physiatrist is to bring these changes towards benefits. As a physiatrist, providing therapy for cerebral palsy to transcend their limitations to be able to perform activity and participation well in life is essential. One of the recommended therapies for person with cerebral palsy is full-body movement exercises, such as dance therapy. Dance therapy can be an option with many benefits to help person with cerebral palsy cope with their disability, as well as a source of recreation and social activity. Dance skills can increase self-confidence while improving the function of limbs. One of Indonesia's traditional cultural dances is the Jaipong dance, which originated in West Java, Indonesia. Jaipong dance performances require good coordination between dance movements and music to produce the beauty and elegance of traditional cultural dance. The application of dance therapy in the form of Jaipong dance for cerebral palsy aims to improve motor function, balance, walking patterns, and cardiovascular capacity, with the ultimate goal of helping person's participation in society. In conclusion, the application of Jaipong dance intervention as dance therapy for cerebral palsy can provide many benefits as well as rising a new star as an effort to preserve traditional Indonesian culture, regardless of one's disability status.
Keywords: cerebral palsy; dance therapy; rehabilitation